Thermoelectric modules built using ceramic legs grown by laser floating zone. Issue 15 (15th October 2020) - Ferreira, N.M.; Lopes, D.; Kovalevsky, A.V.; Costa, F.M.; Sotelo, A.; Madre, M.A.; Rezania, A.
Abstract: The present work reports the first attempt of thermoelectric module design, based on oxide materials grown through the laser floating zone technique. Two modules with 4-legs thermoelectric were assembled using Bi2 Ba2 Co2 Oy fibres as p-type legs, while Ca0.9 La0.1 MnO3 and CaMn0.95 Nb0.05 O3 fibres were used as n-type legs. Structural and electrical characterisation of the individual fibres was performed, and the results compared to the literature. The evolution of open-circuit voltage on heating and cooling up to 723 K, present the expected trends based on the Seebeck coefficient of the individual fibres, suggesting good reliability of the modules during temperature cycling. The power generation performance was evaluated for a temperature difference up to 500 K under different electric loads. The maximum measured power was 2.2 mW for a module volume of 39 mm 3 . Nevertheless, the module here studies possess better performance than those commercially available.